Pembelajaran Remedial sebagai Upaya Mengurangi Kesulitan Belajar Matematika Siswa MTsN 2 Banda Aceh di Rumah - Vina Halizayanti.F; Lukman Ibrahim; Rosmila Dewi (Jurnal Riset dan Pengabdian Masyarakat, 2022)
The purpose of this study is to describe and explain the implementation of remedial learning in mathematics at MTsN 2 Banda Aceh. This research is a case study of the qualitative approach. The subjects in this study were teachers, students of class VII-2 who were determined based on the results of the test during preliminary study with the lowest score that their parents were less able to guide their children in learning mathematics at home, and parents of the students of the subjects. The methods of data collection were observation, interview and documentation. Activities related to the implementation of remedial mathematics learning are those that are studied. The data validity technique is triangulation of sources and methods and the data was analyzed by using descriptive qualitative techniques. The results of this study indicate that the tutorial is very helpful in understanding the material and tasks given by the teacher. Students who usually can't do anything to being able to because of their behavior change to be quite active asking questions during the tutorial learning. However, the assessment given by the teacher for students who take remedial program is limited to the KKM value so that it is fair and impartial between students who take remedial and students who do not take remedial.